(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rozaki Z, Rahmawati N, Wijaya O, Khoir IA, Senge M, Kamarudin MF. 2021. Perception of agroforestry adopter and non-adopter on volcano risk and hazard: a case in Mt. Merapi, Java, Indonesia. Biodiversitas 22: 3829-3837. Agroforestry is an agricultural system that many people use in mountainous areas. Some experts have proven that this system can become the mitigation strategy in volcano areas. This study analyzes the risk and hazard perception of agroforestry adopters and non-adopters in the Mt. Merapi prone area. 139 agroforestry adopters and 130 non-adopters were randomly taken from four different areas in Mt. Merapi. Results show that both adopters and non-adopters show different perceptions regarding hazards and risk. The effectiveness of agroforestry practice for mitigation strategies needs to be studied more. The awareness of hazards and risks in the Mt. Merapi prone area is essential to save more lives during the eruption. The challenge is how to persuade agroforestry adopters and non-adopters to flee when the big eruption comes. Even though they flee, they still insist on returning home to take care of their livestock, farm, and protect properties. Mitigation education is needed; also, the infrastructure is important in supporting the mitigation efforts.